A protective role of autophagy in fine airborne particulate matter-induced apoptosis in LN-229 cells. (July 2022) - Yuan, Jiali; Mo, Luke; Mo, Yiqun; Zhang, Yuanbao; Zhang, Yue; Zhang, Qunwei
Abstract: Air pollution is a public health threat and global epidemiological studies have shown that ambient air pollutants are closely related to various poor health conditions, including neurodegenerative diseases. Here, we evaluated the toxic effects and the underlying mechanisms of fine airborne particulate matter (PM2.5 ) on human glioblastoma LN-229 cells. Our results showed that exposure of LN-229 cells to PM2.5 (≥ 200 μg/mL) significantly reduced cell viability. PM2.5 exposure increased autophagy, apoptosis, and ROS production in the cells. Pre-treatment with a ROS scavenger, catalase, or depletion of mtDNA (ρ 0 cells) abolished PM2.5 -induced autophagy and apoptosis. PM2.5 exposure also activated MAPK signals in cells, which were blocked by catalase pre-treatment or mtDNA depletion. Furthermore, inhibition of JNK, but not ERK1/2 or p38, attenuated PM2.5 -induced autophagy and apoptosis in cells. Finally, suppression of autophagy with Bafilomycin A1 or Beclin 1 siRNA exacerbated PM2.5 -induced apoptosis, indicating a protective role of autophagy against PM2.5 -induced apoptosis. Our results demonstrated that exposure of LN-229 cells to PM2.5 caused autophagy and apoptosis through PM2.5 -induced ROS generation, mainly by mitochondria, and JNK activation. Autophagy may have a transient protective response in PM2.5 -induced apoptosis. These findings have important implications for understanding the potential neurotoxicity of PM2.5 . Graphical Abstract: ga1 Highlights: PM2.5 caused a dose- and a time-dependent increase in autophagy and apoptosis in LN-229 cells. PM2.5 induced ROS, especially mitochondrial ROS, generation and JNK activation. Pretreatment of the cells with ROS or JNK inhibitor abolished PM2.5 -induced autophagy and apoptosis. PM2.5 -induced autophagy has a transient protective role on PM2.5 -mediated apoptosis.